Design reed controller for MIDI auto-saxophone - Khairunisa, Mohd Kadir (2013)
This project presents the method of designing reed controller for woodwind instrument that is Alto saxophone. In order to produce sound from saxophone, air pressure is blow into the mouthpiece and the reed will vibrate and produce sound wave. As the reed is springy and can bend, a simple mass-spring-damper. system has been developed using Matlab Simulink to model the reed. The correct pitch can be produce by controlling the air pressure and frequency of vibration. Thus, an experiment to define frequency from the reed has been obtained by attached microphone to the mouthpiece. In this way, the physical system of the saxophone reed can be define clearly to provide better approximation parameters to the real instrument. A servo motor is used to control the vibration of the reed as it is moving up and down by receiving MIDI signal from the MIDI decoder. 12V solenoid valve is used to control air pressure come from the air compressor into the mouth cavity. The result is expected to be able to control the air pressure and the vibration of the reed then can produce a nice sound from the MIDI auto-saxophone.